2014
DOI: 10.1002/chem.201304688
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Tetrathiafulvalene–Benzothiadiazole Dyad and Its Highly Symmetrical Charge‐Transfer Salt: Ordered Donor π‐Stacks Closely Bound to Their Acceptors

Abstract: A compact and planar donor-acceptor molecule 1 comprising tetrathiafulvalene (TTF) and benzothiadiazole (BTD) has been synthesised and experimentally characterised by structural, optical and electrochemical methods. Solution processed and thermally evaporated thin films of 1 have also been explored as active material in organic field-effect transistors (OFETs). For these devices, a hole field-effect mobility of FE = (1.3 ± 0.5) ×10-3 cm 2 /Vs and of FE = (2.7 ± 0.4) ×10 -3 cm 2 /Vs could be determined for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 47 publications
2
36
1
Order By: Relevance
“…Notably, at approximately 120 K and 50 K, two clear‐cut irregularities occur in the susceptibility data. This kind of behavior is intriguing; the sudden drop in χ occurs at approximately 120 K, close to the observed discontinuity in the conductivity regime,9c thus suggesting that these two observations are directly linked.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…Notably, at approximately 120 K and 50 K, two clear‐cut irregularities occur in the susceptibility data. This kind of behavior is intriguing; the sudden drop in χ occurs at approximately 120 K, close to the observed discontinuity in the conductivity regime,9c thus suggesting that these two observations are directly linked.…”
mentioning
confidence: 73%
“…Owing to an energetically low‐lying charge‐transfer state, they absorb strongly in the visible spectral region and are characterized by a HOMO–LUMO gap in the order of 2 eV. It was also found that the partially oxidized and crystalline compound, {(TTF–BTD) 2 I 3 }, is semiconducting, exhibiting a fairly large room‐temperature conductivity of 2 S cm −1 and activation energies in the range of 150–100 meV 9c. This observation is accounted for by the slightly dimerized π stacking of (TTF–BTD) +0.5 molecules within the crystalline solid.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This conducting behavior is more often accomplished in materials displaying segregated stacks, in which the D-A pairs are better overlapped. [8][9] For the opposite reason, a polymorph with alternated stacks will mostoften be insulator. 10 In other words, the conducting properties of charge transfer salts based on two components are highly susceptible to the presence of polymorphism.…”
Section: Introductionmentioning
confidence: 99%